"Fear of Missing Out or Fair Price? Understanding Drivers of Hydroponic Melon Purchase Intention in Gemolong" - sitti muallimah Sitti (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2026)
ABSTRACT - The purpose of this study is to analyze the influence of price, knowledge, and the Fear of Missing Out (FOMO) phenomenon on consumer purchasing interest in hydroponic melons in Gemolong. The background of this study is based on the increasing public awareness of health, environmental, and sustainable lifestyle issues that have driven the demand for modern agricultural products such as hydroponics. This study uses a quantitative approach with primary data obtained through distributing questionnaires to 100 respondents who bought hydroponic melons. Data were analyzed using multiple linear regression methods with the help of SPSS version 25 software . The results of the study show that the regression model has an R² value of 0.281 , which means that the price, knowledge, and FOMO variables are able to explain 28.1% of the variation in consumer purchasing interest , while the rest is influenced by other factors outside the model. Simultaneously, the three independent variables have a positive and significant effect on purchasing interest ( F count = 12.481; Sig = 0.000 <0.05 ). However, partially, only the price variable has a positive and significant effect on purchasing interest (t count = 2.258; Sig = 0.026 <0.05 ), while knowledge (Sig = 0.063) and FOMO (Sig = 0.564) have a positive but insignificant effect. These findings indicate that price is the dominant factor influencing consumer purchasing interest in hydroponic melons in Gemolong, while knowledge and FOMO are not yet the primary drivers of purchasing decisions. This research offers practical implications for hydroponic agribusinesses to establish competitive pricing strategies and increase public awareness of the benefits and sustainability of hydroponic products. Keywords: Price, Knowledge, FOMO, Purchase Interest, Hydroponic Melon